2000
DOI: 10.1152/jappl.2000.89.6.2344
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cutaneous receptor stimulation on muscular atrophy developed in hindlimb unloading condition

Abstract: The aim of this study was to investigate whether stimulation of the cutaneous mechanoreceptors of the rat foot sole could partially or totally prevent the soleus muscle atrophy developed after 14 days in hindlimb unloading conditions. Final experiments were achieved under deep anesthesia using pentobarbital sodium (60 mg/kg, ip injection). Atrophy was characterized by a significant decrease in muscle wet weight, fiber size, maximal twitch and tetanic tensions, contraction kinetics, and histochemical and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…In simulated microgravity, the patterns transmitted by these cutaneous receptors are likely to be disrupted because the soles of the feet are not in contact with the ground; consequently, the nervous motor message could be modified by the reflex pathway. The dynamic cutaneous mechanoreceptor stimulation of the plantar surface of the rat hindfeet during the 14 days of HU partially prevented soleus atrophy (De-Doncker et al, 2000;Kyparos et al, 2005). These studies demonstrated that, in HU condition, plantar cutaneous afferent information was decreased and participated in the development of muscular atrophy.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…In simulated microgravity, the patterns transmitted by these cutaneous receptors are likely to be disrupted because the soles of the feet are not in contact with the ground; consequently, the nervous motor message could be modified by the reflex pathway. The dynamic cutaneous mechanoreceptor stimulation of the plantar surface of the rat hindfeet during the 14 days of HU partially prevented soleus atrophy (De-Doncker et al, 2000;Kyparos et al, 2005). These studies demonstrated that, in HU condition, plantar cutaneous afferent information was decreased and participated in the development of muscular atrophy.…”
mentioning
confidence: 65%
“…Consequently, the nervous motor message could be modified. This hypothesis has been confirmed by experiments that used the stimulation of plantar cutaneous mechanoreceptors, since the stimulation of these receptors during the HU period prevents 53% muscular atrophy (De-Doncker et al, 2000) indicating that plantar cutaneous information is greatly decreased during HU. Concerning the implication of proprioceptive information, Riley et al (1990) have observed that in HU conditions, the soleus was often in a shortened position as after tenotomy and immobilization in a plantar flexion position.…”
Section: Immediately After Humentioning
confidence: 76%
See 1 more Smart Citation
“…When the motor nerve was connected end-to-end to the sensory nerve ("Sensory protection"), it seemed to provide trophic environment to minimize muscle atrophy until a motor donor nerve became available. Although incapable of forming excitable neuromuscular junctions, sensory nerves were found to exert powerful trophic effects on denervated muscle fibers [12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, various preventive interventions can be implemented before exposure to the atrophic environment (Fujino et al, 2009) and during immobilization (De-Doncker et al, 2000;Kyparos et al, 2005). A previous study in the mouse immobilized the ankle joint at the maximum dorsiflexion and the maximum plantarflexion positions with a cast and assessed muscle atrophy in the tibialis anterior and soleus muscles (Fujita et al, 2009).…”
Section: Introductionmentioning
confidence: 99%